2019
DOI: 10.1111/dme.13960
|View full text |Cite
|
Sign up to set email alerts
|

Persistent C‐peptide is associated with reduced hypoglycaemia but not HbA1c in adults with longstanding Type 1 diabetes: evidence for lack of intensive treatment in UK clinical practice?

Abstract: Aims Most people with Type 1 diabetes have low levels of persistent endogenous insulin production. The Diabetes Control and Complications Trial showed that close to diagnosis preserved endogenous insulin was associated with lower HbA1c, hypoglycaemia and complication rates, when intensively treated. We aimed to assess the clinical impact of persistent C‐peptide on rate of hypoglycaemia and HbA1c in those with long duration (> 5 years) Type 1 diabetes. Methods We conducted a cross‐sectional case–control study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
35
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 25 publications
(55 reference statements)
11
35
3
2
Order By: Relevance
“…Size of dot corresponds to age at diagnosis. Horizontal lines represent 10 pmol/l and 50 pmol/l thresholds with findings from several previous investigations [9][10][11], although significant differences were limited to asymptomatic hypoglycaemia in our study. Marren et al [9] describe significant differences in self-reported symptomatic and asymptomatic hypoglycaemia in those with preserved C-peptide, although the median C-peptide concentration in this group (114 pmol/l) was substantially higher than in our study (32 pmol/l).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Size of dot corresponds to age at diagnosis. Horizontal lines represent 10 pmol/l and 50 pmol/l thresholds with findings from several previous investigations [9][10][11], although significant differences were limited to asymptomatic hypoglycaemia in our study. Marren et al [9] describe significant differences in self-reported symptomatic and asymptomatic hypoglycaemia in those with preserved C-peptide, although the median C-peptide concentration in this group (114 pmol/l) was substantially higher than in our study (32 pmol/l).…”
Section: Discussionsupporting
confidence: 72%
“…Horizontal lines represent 10 pmol/l and 50 pmol/l thresholds with findings from several previous investigations [9][10][11], although significant differences were limited to asymptomatic hypoglycaemia in our study. Marren et al [9] describe significant differences in self-reported symptomatic and asymptomatic hypoglycaemia in those with preserved C-peptide, although the median C-peptide concentration in this group (114 pmol/l) was substantially higher than in our study (32 pmol/l). While we report random plasma C-peptide and Marren et al [9] used values after a standard mixed-meal tolerance test, the correlation between random and post-mixed-meal C-peptide is known to be very strong (R = 0.91) and is unlikely to substantially limit the comparability of these studies [18].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, the subgroup with the lowest FCP identified patients who were more vulnerable to hypoglycaemia despite requiring lower basal insulin doses, presumably related to impaired glucose counter‐regulation with deficient glucagon responses to hypoglycaemia consequent to pancreatic islet beta‐ and alpha‐cell dysregulation . Interestingly, even at persistently low FCP levels (0.02 nmol/L) in people with type 1 diabetes mellitus (T1DM), small differences of FCP above or below 0.02 nmol/L may contribute to changing the risk of hypoglycaemia . Therefore, groups/phenotypes with low or very low FCP levels in T2DM and particularly in T1DM, respectively, require a more cautious approach to initiating and titrating basal (and prandial) insulin to limit the risk of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…24 Interestingly, even at persistently low FCP levels (0.02 nmol/L) in people with type 1 diabetes mellitus (T1DM), small differences of FCP above or below 0.02 nmol/L may contribute to changing the risk of hypoglycaemia. 25 Therefore, groups/phenotypes with low or very low FCP levels in T2DM and particularly in T1DM, respectively, require a more cautious approach to initiating and titrating basal (and prandial) insulin to limit the risk of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%